Performance analysis of noncoherent digital delay locked loops for direct sequence spread spectrum systems with Doppler shift and quantized adaptation. - Wern-Ho Sheen (IEEE Transactions on wireless communications)
The noncoherent second-order digital delay locked loop (DLL) with the presence of Doppler shift is investigated. The loop performance such as lock-in range, transient response, mean time-to-lose lock (MTLL), and mean square tracking error (MSE) are analyzed. The analysis is unique in two respects. First, MTLL and MSE are evaluated more accurately than by previous methods. Second, the impact of quantized adaptation on the loop performance is examined for digital DLL that was neglected previously. Numerical results show that: 1) the quantized adaptation may significantly alter the loop behaviors, including the lock-in range, transient responses, MTLL, and MSE; and 2) the traditional analysis based on Gaussian approximation may result in a large error in performance evaluation when quantized adaptation is taken into account.